First synthesis and absolute configuration of phorbasin H, a diterpene carboxylic acid isolated from the sponge Phorbas gukulensis. Issue 12 (2nd December 2019) - Takahashi, Kensuke; Ogura, Yusuke; Kuse, Masaki; Takikawa, Hirosato
ABSTRACT: The first synthesis of phorbasin H, a diterpene carboxylic acid isolated from the sponge Phorbas gukulensis, was achieved using 1, 4- trans -cyclohexanedimethanol and ( S )-citronellal as starting materials. The data collected in this synthesis indicated the absolute configuration of the naturally occurring phorbasin H to be S .